Case reportSegmental Darier’s disease – case report - Erkiert-Polguj, Anna; Omulecki, Anastazy; Waszczykowska, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
A 54-year-old woman with brown, hyperkeratotic papules on the right, anterior part of her trunk for 4 years is described. Diagnosis of segmental Darier’s disease was based on clinical manifestation and histological findings (focal acantholysis and dyskeratosis). Literature data of pathogenesis and therapeutic options are also described. This case report is presented because of the rarity and diagnostic problems of segmental Darier’s disease.